Evaluasi Program Beasiswa Bagi Mahasiswa Kabupaten Pegunungan Bintang Menggunakan Model Goal Oriented Evaluation - Tabuni, Nanita; Tri Satyawati, Sophia; Ismanto, Bambang (Universitas Kristen Satya Wacana, 2024)
This research aims to evaluate the Papua Bintang Mountains Regency Regional Government scholarship program for students at Satya Wacana Christian University using the Goal Oriented Evaluation Model (Tyler). The research approach uses mixed methods. The research subjects were star mountains students, managers and assistants of the scholarship program. The research sample was 50 student respondents who received scholarships. Qualitative data analysis techniques: interviews, document studies and observations, and questionnaires. Qualitative data analysis techniques include: data reduction, data presentation, and drawing conclusions. Quantitative data analysis techniques use percentages and categories. The results of the research from 7 (stages) can be concluded: The formulation of objectives includes general objectives and specific objectives, general objectives include: improving the quality of human resources for regional sons and daughters and after graduating they will return to develop their region, measured after students graduate, and specific objectives include: academic achievement in the form of Index Cumulative Achievement in 2022/2023 with an average of 2.25. the ability to build academic cultural character in the sufficient category, the ability to build self-confidence with sufficient hatred, and the ability to adapt in the high category. This shows that the achievement of goals has increased after 3 years of college students.